PARTISIPASI PUBLIK DALAM REKRUTMEN CPNS: MASALAH DAN KEMUNGKINAN - Istianda, Meita; Putra, Muslimin (LPPM Universitas Terbuka, 2006)
This article is focused on Good Corporate Governance study, especially on the behalf of public participation dimension in the government employee recruitment. The case analysis is conducted in qualitative methods during the government employee recruitment in 2005-2006. The case is monitored by the national printed medias. This article generally recommended to open the opportunities of public participation in the management of employee affairs. This article also to open access for public in order to supervise the implementation of government employee recruitment to minimize the irregularity of this process.